GEOLOGIA ESTRATIGRAFIA Y PALEONTOLOGIA DE LA REGION DE CACAHUAMILPA MEXICO - MULLERRIED, FEDERICO KG (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1948)
A general review with special emphasis on root rots of corn and of small grains, corn diseases, chemusco or sigatoka of bananas, rusts of wheat, organization and education
AN ESC NAC CIENC BIOL
Keywords: GEOLOGIA, ESTRATIGRAFIA, PALEONTOLOGIA, REGION DE CACAHUAMILPA, MEXICO; CIENCIAS DE LA VIDA; PALEONTOLOGIA; PALEONTOLOGIA ANIMAL